Tinjauan Astronomis Penetuan Awal Tahun Kalender Rowot Sasak Berdasarkan Kemunculan Bintang Pleiades - Kohar, Abdul; Taufikurrahman, Arief (Universitas Islam Negeri Mataram, 2020)
The appearance of the Pleiades or Rowot (sasak) stars at dawn in the northeast horizon serves as a marker for the beginning of the year. Determination of its appearance based on urfi reckoning with methods 5-15-25 synchronized with the lunar calendar and appeared in May synchronized with the solar calendar. The author is interested in studying the patterns 5-15-25 as determining the appearance of rowot / pleiades stars at dawn which has become a habit of observing them and the main configuration in the preparation of the Rowot Sasak calendar. Proving the pattern in the long run requires astronomy as its parameter. Based on this background, the authors formulate the problem. How to determine the beginning of the year in the Rowot Sasak calendar system? How is the determination of the beginning of the calendar year rowot sasak reviewed in an Astronomy perspective? This research is a field research (Field Research) with rowot sasak calendar and the results of interviews with competent experts as primary data. The analysis used is descriptive qualitative, by describing the determination of the beginning of the year in the rowot sasak calendar based on the appearance of the Pleiades star then analyzed by the method of determining the appearance of stars astronomically. The results of this study are firstly, the 5-15-25 pattern or coincides in May as a reference in determining the appearance of rowot / Pleiades stars using traditional reckoning sourced from observations over the long term of the Sasak ancestors. Determination of the beginning of the year based on the appearance of rowot / Pleiades stars is used to mark the season or the first month of sasak calendar. Second, astronomically with epoch j2000, rowot / Pleiades stars have 3h48m28.6s right ascension and declination + 24d06m19s results in rowot / Pleiades stars not being observed at the beginning of the dawn of May as previously practiced, but with astronomical data the rowot / Pleiades star can observed starting around 7 June at 05.30 already above the northeastern horizon. Kemunculan bintang Pleiades atau Rowot (sasak) pada waktu subuh di ufuk timur laut dijadikan sebagai penanda awal tahun. Penentuan kemunculannya berdasarkan hisab urfi dengan pola 5-15-25 disinkronkan dengan kalender hijriah dan muncul pada bulan Mei disinkronkan dengan kalender masehi. Penulis tertarik mengkaji pola 5-15-25 sebagai penentuan kemunculan bintang rowot/pleiades pada waktu subuh yang sudah menjadi kebiasaan mengamatinya dan konfigurasi utama dalam penyusunan kalender Rowot Sasak. Pembuktian pola tersebut dalam jangka waktu panjang membutuhkan ilmu astronomi sebagai parameternya. Berdasarkan latar belakang tersebut, penulis merumuskan masalahnya. Bagaimana penentuan awal tahun dalam sistem penanggalan rowot sasak? Bagaimana penentuan awal tahun kalender rowot sasak ditinjau dalam perspektif Astronomi? Penelitian ini bersifat lapangan (Field Research) dengan kalender rowot sasak dan hasil wawancara dengan ahli yang berkompeten sebagai data primer. Analisis yang digunakan adalah deskriptif kualitatif, dengan mendeskripsikan penentuan awal tahun dalam kalender rowot sasak berdasarkan kemunculan bintang Pleiades kemudian dianalisis dengan metode penentuan kemunculan bintang secara astronomi. Temuan dari hasil penelitian ini adalah pertama, pola 5-15-25 atau bertepatan pada bulan Mei sebagai acuan dalam menentukan kemunculan bintang rowot /Pleiades menggunakan hisab yang tradisional bersumber dari hasil pengamatan dalam jangka waktu panjang nenek moyang bangsa sasak. Penentuan awal tahun berdasarkan kemunculan bintang rowot/Pleiades digunakan untuk penanda musim atau bulan pertama penanggalan sasak. Kedua, secara astronomi dengan epoch j2000, bintang rowot/Pleiades memiliki aksensiorekta 3h48m28.6s dan deklinasi +24d06m19s mengakibatkan bintang rowot/Pleiades tidak dapat diamati pada awal kemunculannya waktu subuh bulan Mei sebagaimana sebelumnya dipraktikkan, namun dengan data astronomi tersebut bintang rowot/Pleiades dapat diamati dimulai sekitar tanggal 7 juni pada pukul 05.30 sudah diatas ufuk timur laut.